Caraterização físico-química e avaliação dos compostos bioativos de óleos brutos e refinados de soja, canola, milho e girassol - Freitas, Irene Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Oils are frequently used in human food. Therefore, there is need to check the quality and know their bioactive substances, since during the stages of commercial refining not only undesirable components are removed but also the desirable compounds. The objective of this study was to evaluate crude and refined soybean, canola, corn and sunflower oils of five different brands sold in the Brazilian market. The physicochemical characterization through the analysis of free fatty acids, peroxide index, p-anisidine index, totox value, specific extinction, unsaponifiable matter and oxidative stability index was carried out. The bioactive compounds were determined through the analysis of phytosterols, tocopherols, carotenoids, phenolic compounds and fatty acid composition. The antioxidant activity was evaluated by the ABTS●+ DPPH●, FRAP and β-carotene/linoleic acid systems. The obtained data was submitted to analysis of variance at the 1% significance level, followed by the Tukey test at a 5% probability level. Through the physicochemical analysis, the crude oils can be considered of good quality. During refining removal of undesirable compounds such as free fatty acids and peroxides indices occurred as expected. Moreover, this process reduced, on average, 22-42% of unsaponifiable matter. In general, the crude oils analyzed may be considered sources of bioactive compounds. However, during the evaluation of the refined oils, these compounds were removed during the different refining steps used by the industries. Such losses ranged, on average, from 13-30% for total phytosterols, 14-57% for total tocopherols, 54-90% for carotenoids and 26-58% for total phenolic compounds. After refining, corn oil stood out as having an average of 945.68 mg/100 g and 127.82 mg/kg of phytosterols and Total phenolic compounds, respectively, and soybean oil with 503.22 mg/kg of total tocopherols. Losses varied even between different brands for the same ...

Os óleos são usados com frequência na alimentação humana. Por isso há necessidade de verificar a qualidade e de conhecer as suas substâncias bioativas, pois nos estágios da refinação comercial ocorre a remoção não somente de componentes indesejáveis, mas também compostos desejáveis. O objetivo deste trabalho foi avaliar óleos brutos e refinados de soja, canola, milho e girassol de cinco diferentes marcas comercializadas no mercado brasileiro. Foi feita a caracterização físico-química por meio das análises de ácidos graxos livres, índice de peróxidos, índice de p-anisidina, valor totox, extinção específica, matéria insaponificável e índice de estabilidade oxidativa. Os compostos bioativos foram determinados através das análises de fitosteróis, tocoferóis, carotenoides totais, compostos fenólicos totais e composição em ácidos graxos. A atividade antioxidante foi avaliada por meio dos sistemas ABTS●+, DPPH●, FRAP e β-caroteno/ácido linoleico. Os dados obtidos foram submetidos à análise de variância no nível de 1% seguida do teste de Tukey no nível de 5% de probabilidade. Pelas análises físico-químicas, os óleos brutos podem ser considerados de boa qualidade. Na refinação houve remoção de compostos indesejáveis, tais como ácidos graxos livres e índices de peróxidos, conforme esperado. Por outro lado, este processo reduziu, em média, de 22-42% de matéria insaponificável. De maneira geral, os óleos brutos analisados podem ser considerados fontes de compostos bioativos. No entanto, avaliando os óleos refinados, houve remoção destes compostos durante as diferentes etapas de refinação utilizadas pelas indústrias. Tais perdas variaram, em média, de 13-30% para fitosteróis totais, 14-57% para tocoferóis totais, 54-90% para carotenoides totais e 26-58% para compostos fenólicos totais. Após a refinação, o óleo de milho se destacou apresentando, em média,...
Keywords: Chemistry, Physical and theoretical; Tecnologia de alimentos; Físico-química; Óleos vegetais - Análise; Compostos bioativos; Antioxidantes